PERTIMBANGAN HAKIM DALAM MENERAPKAN ALAT BUKTI PETUNJUK DALAM MENJATUHKAN VONIS HUKUMAN PADA TINDAK PIDANA PERTAMBANGAN EMAS ILEGAL DI KABUPATEN KUANTAN SINGINGI - Nanda Efrialis; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Based on the author's observations in the field, it can be seen that in the illegalgold mining area there are former mining excavations in the form of small lakes filledwith yellow-brown water, beside the holes are piled hundreds of cubic stones mixedwith sand from mining residue, while the trees around it looks dry. The law explainsthat the minimum prison term for activities related to the environment is one year, sothat according to the author's assumption, the application of threats in one of thesample cases is less effective. Law enforcement is the efforts taken by the government oran authority to ensure the achievement of a sense of justice and order in society byusing several devices or tools of power, both in the form of laws, to law enforcersincluding the police, judges, prosecutors, and others. lawyer.When viewed from the type, this research is classified as sociological legalresearch, namely research obtained directly from the community or primary dataresearch. The data collection method in this research is the documentation method. Tocollect the data referred to above, the following techniques were used: Libraryresearch. This is done by searching, recordifng, taking inventory, studying data in theform of library materials, and analyzing these data. Observation is a complex process,a process composed of various biological and psychological processes. Observationcan also be said as a method carried out by direct observation of the object of research.From the results of the research and discussion of considerations adjusted toArticle 158 of the Law of the Republic of Indonesia Number 3 of 2020 concerningAmendments to Law Number 4 of 2009 concerning Minerals and Coal in conjunctionwith Article 55 paragraph (1) 1 of the Criminal Code, the elements of the panel ofjudges are considering Not “everyone”, Not “who conducts mining without a permit”,Who commits, orders to do, or participates in carrying out actions. The obstaclesencountered in the application of the evidence guide for judges in passing a criminaldecision on illegal gold mining in Kuantan Singingi Regency consisted of theperpetrators not recognizing the evidence and the difficulty of evacuating the evidence.Keywords: Criminal, Judge's Consideration, and Illegal Gold Mining